THE SYNTACTICAL CATEGORIES OF PHRASE IN FOUR SONGS LYRICS FROM ADELE’S 25 ALBUM - Wina Siti Karmila (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2022)
English song is not only as an entertainment for the listener to enjoy the music and following the song (singing), but also as a means of learning containing full of knowledge. For example, people are able to relearn sentence structure (grammatical), enrich their vocabulary, train to pronunciation, and many more by listening and learning the song. The aspect of this analysis is Adele’s songs’ lyrics from 25 album. Adele is one of famous singer from England, her 25 album has many awards, and it albums became the world’s best-selling album in 2015. The researcher focuses on one the linguistics study, syntax. More specifically, it is about the syntactical categories of phrase because phrase is the basis of sentences building. Additionally, student or common people who learn English before learning about sentence more, it is better to learn about phrases previously. The aims of this research are describing kinds of syntactical categories of phrases and finding out the dominant syntactical categories of phrase found in Adele’s songs’ lyrics. The descriptive qualitative method was used for describing, analyzing, and interpreting the data taken from four songs’ lyrics of the album. The data were all of words and sentences that consist of songs’ lyrics by Adele in 25 album. The technique of collecting data was used documentary and library research. Kind of phrase theory proposed by Thomas and Phrase Structure Rules theory was used to analyze the data. From the data analysis, it shows that there are five kinds of phrase in Adele’s 25 album. There are noun phrase 50%, verb phrase 28%, prepositional phrase 11%, adjective phrase 4%, and adverb phrase 7%. The result shows that noun phrase is the dominant phrase in Adele’s 25 album. It was supported by the using of transitive verb as the dominant verb in Adele’s song lyrics since the phrase which present after verb that is noun phrase as a direct object. Then, noun phrase also commonly has two functions in the sentences such as the subject and the object. In conclusion, noun phrase is mostly found because the singer wants to mention many things of her experience and express her feelings in the past. As suggestion, readers should use songs as not only to be listened but also to be learnt.